High-reflective Mulching Membrane for a Sustainable Development: Monitoring Campaign - Manni Mattia; Di Giuseppe Alessia; Petrozzi Alessandro; Nicolini Andrea; Rossi Federico; Cotana Franco (E3S Web of Conferences, 2020)
Modern agriculture techniques are responsible for the production of large volumes of greenhouse gases that represent the main cause of climate change. At the same time, agricultural activities are negatively affected by climate change effects, showing a reduction in productivity. Within this framework, the present study aims at investigating the effectiveness of an innovative high-reflective mulching membrane that can be exploited in the agricultural sector to mitigate its environmental impact. It consists of a mulching membrane coupled to an irrigation system, and painted with bright pigments on the side facing the skydome. This technology was used in food crop farming in the experimental field in Perugia. Sensors for monitoring solar irradiation, rainwater recovery, and phenological parameters were installed. Data collected during the monitoring campaign conducted in summer demonstrated that the high-reflective membrane was capable to increase the ground solar reflectance up to 0.60, while avoiding the utilization of potable water and water from the aquifer to irrigate the crops. An acceleration of the photosynthesis processes was also observed along with an increment in the productivity: tomatoes grew up to 20% more in weight.